Ozanimod Maintenance Therapy After Cyclosporine Induction in Acute Severe Ulcerative Colitis. Issue 7 (21st July 2022) - Cohen, Nathaniel A.; Dalal, Sushila R.; Choi, David; Rubin, David T.
ABSTRACT: Ozanimod has recently received US Food and Drug Administration approval for moderate-to-severe ulcerative colitis. Treatment of acute severe colitis remains a clinical challenge, and although many patients respond to cyclosporine therapy, there remains a relative paucity of maintenance options. This case report describes the first reported, successful use of ozanimod after hospitalization for acute severe ulcerative colitis and in tandem with cyclosporine. Although a longer follow-up is required, this report shows the feasibility of ozanimod in this clinical setting.